PENGARUH PENERAPAN GREEN ACCOUNTING, CORPORATE SOCIAL RESPONSIBILITY, DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN - Anggi Arista (STIE Madani Balikpapan, 2026)
This study aims to analyze the influence of green accounting implementation, corporate social responsibility (CSR), and environmental performance on firm value. With the increasing awareness of environmental and sustainability issues, companies are expected not only to focus on financial aspects but also to consider the environmental and social impacts of their operations. This research uses a quantitative approach with secondary data obtained from annual reports and sustainability reports of companies listed on the Indonesia Stock Exchange. The results show that green accounting and CSR have a positive and significant effect on firm value, while environmental performance also has a positive but not significant effect. These findings indicate that integrating environmentally friendly policies into business strategies can enhance corporate image and provide added value to stakeholders. This research offers important implications for corporate management in developing sustainable business practices.